Television drama and the urban diegesis: portraying Albuquerque in Breaking Bad. Issue 5 (28th May 2018) - Cook, Ian R.; Ashutosh, Ishan
ABSTRACT: Albuquerque, New Mexico is the filming location and setting of the popular television drama Breaking Bad (2008–2013). Albuquerque is not merely a passive backdrop to the action in the show but a focal point of the series. So much so that in the geographical imaginations of many, Albuquerque and Breaking Bad have become synonymous with each other. This paper critically examines the representation of urban life within the show. To do this it draws upon and expands the existing multi-disciplinary literature on cities and films/television. As well as focusing on the influence of setting and filming the show in Albuquerque on the urban diegesis (i.e. the on-screen city), it also examines three visions of Albuquerque that are projected through the show: (1) Albuquerque as a crime-ridden city; (2) Albuquerque as a spatially divided city; and (3) Albuquerque as a city to escape from.